Decline in semen quality of North African men: a retrospective study of 20,958 sperm analyses of men from different North African countries tested in Tunisia over a period of 6 years (2013-2018) - (:unkn) unknown (My University, 2021)
Background According to numerous studies from around the world, semen quality seems to have declined dramatically in recent times. However, the data available on male fertility status and semen quality in North Africa are limited. Aim To investigate the status of semen quality in North-African men and to understand its variations. Subjects & methods 20,958 sperm-analyses (Spermogram - Spermocytogram) of North-African men (19-77 years old) consulting for infertility, performed in a private laboratory of medical analyses (Tunis, Tunisia) over a period of 6 years (2013-2018), were investigated. All patients had at least 1 year of unprotected intercourse with their partners before the test. Statistical analyses were performed using SPSS 22.0 software for windows. Results Libyan men presented a clear decline in all sperm parameters. A continuous decline in sperm morphology quality was shown in Tunisian and Algerian men. Mauritanian men presented a significant increase in sperm vitality with pseudo-stability in the rest of the sperm parameters during the whole study period. Conclusion North-African men presented remarkable decreases in their semen quality over the last decade. This data could confirm possible global common-causes that need to be identified in order to limit their negative impact on sperm quality, and consequently on male-fertility.
Keywords: African Research